2017
DOI: 10.1021/acs.jpcc.7b07314
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Transitions in Highly Symmetric Au130 Nanoclusters by Spectroelectrochemistry and Ultrafast Spectroscopy

Abstract: Rich and discrete energy states in gold nanoclusters enable different combinations of electronic transitions and correspondingly electrochemical and optical properties for a variety of applications. The impacts on those electronic transitions by the emergence and magnitude/ alignment of a band gap and by the contributions from different atomic/molecular orbitals require further study. Au nanoclusters with 130 core Au atoms are of interest in this report because they are at the transition size regime where a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 39 publications
(61 reference statements)
2
27
0
Order By: Relevance
“…The slower 15.9 ps process is assigned to the relaxation from the lowest excited‐state to the ground state. Previous ultrafast spectroscopic studies revealed the long components of thiolate‐protected NCs with about 100 metal atoms to be 420 ps for Au 103 S 2 (SR) 41 , 180 ps for Au 130 (SR) 50 , 30 ps for Au 133 (SR) 52 , and 325 ps for Ag 146 Br 2 (SR) 80 , which are all significantly longer than 15.9 ps observed in Au 130− x Ag x . Considering the observed charge transfer in XAFS analysis, the shorter excited‐state lifetime of Au 130− x Ag x could originate from its bimetallic nature.…”
Section: Figurementioning
confidence: 87%
See 1 more Smart Citation
“…The slower 15.9 ps process is assigned to the relaxation from the lowest excited‐state to the ground state. Previous ultrafast spectroscopic studies revealed the long components of thiolate‐protected NCs with about 100 metal atoms to be 420 ps for Au 103 S 2 (SR) 41 , 180 ps for Au 130 (SR) 50 , 30 ps for Au 133 (SR) 52 , and 325 ps for Ag 146 Br 2 (SR) 80 , which are all significantly longer than 15.9 ps observed in Au 130− x Ag x . Considering the observed charge transfer in XAFS analysis, the shorter excited‐state lifetime of Au 130− x Ag x could originate from its bimetallic nature.…”
Section: Figurementioning
confidence: 87%
“…Thef aster 1.5 ps process is assigned to internal conversion since the excitation (480 nm, 2.58 eV) is far above the band gap (< 1eV, exact E g not determined). Thes lower 15.9 ps process is assigned to the relaxation from the lowest excited-state to the ground state.P revious ultrafast spectroscopic studies revealed the long components of thiolateprotected NCs with about 100 metal atoms to be 420 ps for Au 103 S 2 (SR) 41 , [16] 180 ps for Au 130 (SR) 50 , [25] 30 ps for Au 133 -(SR) 52 , [26] and 325 ps for Ag 146 Br 2 (SR) 80 , [27] which are all significantly longer than 15.9 ps observed in Au 130Àx Ag x . Considering the observed charge transfer in XAFS analysis, the shorter excited-state lifetime of Au 130Àx Ag x could originate from its bimetallic nature.Further spectroscopic studies on bimetallic NCs are expected to reveal the origin of this faster relaxation than homometal NCs,s uch as the effect of structure,l igands,o rA u/Ag ratios.S uch efforts will be essential in exploring the transition from non-metallic to metallic state in alloy NCs.…”
Section: Methodsmentioning
confidence: 97%
“…Both differential pulse voltammetry (DPV) and square wave voltammograms (SWV) have been used to investigate the electronic structures of Au NCs. , By subtracting the charging energy (potential spacing between successive oxidation or QDL peaks) from the electrochemical gap, one can estimate the HOMO–LUMO gap of a Au NC. In 2017, Kwak et al investigated the electrochemical properties of six Au NCs (Au 25 , Au 38 , Au 67 , Au 102 , Au 144 , and Au 333 ) using the SWV method .…”
Section: Criteria For Determination Of the Molecular State And Metall...mentioning
confidence: 99%
“…For those very large metallic Au NPs (>3 nm), there is no peaks in SWV or DPV, and thus E g → 0. For those sizes in the transition regime with QDL features (∼150–300 gold atoms), one will observe almost evenly spaced peaks, and thus, it is difficult to determine if they are in the metallic state or not, and additional characterization methods are needed.…”
Section: Criteria For Determination Of the Molecular State And Metall...mentioning
confidence: 99%
“…The similarity between the absorption spectra of [Au 133 (TBBT) 52 ] 0 and [Au 133 (TBBT) 52 ] + may be ascribed to the much less perturbation of one electron loss in Au 133 (1 out 81e) than Au 25 (1 out of 8e) as well as possibly less structural distortion in Au 133 than Au 25 when switching the charge state. 46,56,57 We also performed electrochemical oxidation of [Au 133 (-TBBT) 52 ] 0 by applying positive voltages and monitored the optical spectra in situ, 68,69 but no change in optical spectra was found, even aer applying a 1 V bias for 90 min (Fig. S1 †).…”
Section: ] +mentioning
confidence: 99%